Line Spread Test Results for Commercially Available the White Rice Porridge with Salmon - Including the Effect of Four Types of Thickening Agents Added after Blending - (Global Journal of Medical Research, 2023)
Commercially available porridge containing ingredients meat fish vegetables etc has a high nutritional value and is very useful both daily and in the event of a disaster By making porridge into a uniform liquid porridge with a mixer baby food and people with weak chewing ability can eat it Uniform liquid porridge poses a risk of aspiration for people with impaired swallowing function In this study we report the result of making the white rice porridge with salmon into a uniform liquid porridge with a mixer and adding four different types of Thickener to increase the viscosity By adding salmon as an ingredient the amount of protein was higher than that of white rice porridge By adding two types of Thickener containing dextrin and calcium lactate the viscosity remained stable over time The type of thickening agent that stabilizes the viscosity varies depending on the nutrients contained in the porridge we would like to study more combinations of porridge and thickening agents in the future
Keywords: commercial product; white rice porridge with salmon; lin spread test (LST); thickener